pophelper: an R package and web app to analyse and visualize population structure - Francis, R. M. (Molecular ecology resources, 2017)
The pophelper r package and web app are software tools to aid in population structure analyses. They can be used for the analyses and visualization of output generated from population assignment programs such as admixture, structure and tess. Some of the functions include parsing output run files to tabulate data, estimating K using the Evanno method, generating files for clumpp and functionality to create barplots. These functions can be streamlined into standard r analysis workflows. The latest version of the package is available on github (https://github.com/royfrancis/pophelper). An interactive web version of the pophelper package is available which covers the same functionalities as the r package version with features such as interactive plots, cluster alignment during plotting, sorting individuals and ordering of population groups. The interactive version is available at http://pophelper.com/.